Patellar Giant-Cell Tumor: a Case Report - Irsan, Istan Irmansyah; Persada, Satria Pandu; Aditya, Rakhmad (The Journal of Experimental Life Science, 2018)
Giant cell tumor (GCT) found mostly in the long bones metaphysis or epiphysis. GCT usually occur between the ages of a third and fourth decade and locally aggressive. Giant-Cell Tumor seldom affects the patella. Multicentric forms rarely reported. A fourteen-year-old female with a lump at her left patella since one-year associated with slight pain that aggravated by activity for six months. Plain X-ray left knee AP, and lateral views reveal expansile lytic lesion in left patella with thinning of the anteroinferior cortex and sclerotic septa within. MRI of left knee shows approximately 3x2x2 cm heterogeneous lobulated expansile soft tissue mass in left patella extending up to the patellofemoral joint with fluid-fluid appearance. From fine needle aspiration cytology, resulting giant-cell tumor with the differential diagnosis of an aneurysmal bone cyst. The operation already performed. Curettage, bone graft, and a biopsy taken. An immunocytochemical smear was performed and confirmed as a patellar giant-cell tumor. Six months after excision of the tumor, the patient complained no arthralgia and have a full range of motion for the knee. Keywords: Giant-cell tumor, knee lump, knee pain, patella